BIOGRAPHY AND CONTRIBUTION TO SCIENCE OF BAZARGUR DAMBA (1932- 2017), HONORARY MEMBER OF MONGOLIAN SCIENCE, DOCTOR OF SCIENCE, PROFESSOR, AND RESEARCHER ON CHINGGIS KHAAN (Mongolian Journal of Geography and Geoecology, 2022)
ШИНЖЛЭХ УХААНЫ ГАВЬЯАТ ЗҮТГЭЛТЭН, ШИНЖЛЭХ УХААНЫ ДОКТОР, ПРОФЕССОР, ЧИНГИС ХААН СУДЛААЧ ДАМБЫН БАЗАРГҮРИЙН НАМТАР, ШИНЖЛЭХ УХААНД ОРУУЛСАН ХУВЬ НЭМЭР (1932-2017)